Potential High-Risk Drug-Drug Interactions Among Elderly Outpatients With Dementia: A Cross-Sectional Study - Felipe Ferreira; Julia Silva Valério Diniz; Patrícia Medeiros-Souza; Marco Polo Dias Freitas; Einstein Francisco Camargos; Liana Tieko Evangelista Kusano; Leopoldo Luiz dos Santos-Neto (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To analyse the occurrence of potential high-risk drug-drug interactions in elderly individuals with dementia. METHODS: The sample was chosen from a geriatric outpatient clinic of the Multidisciplinary Center for the Elderly in the University Hospital of Brasília. This cross-sectional study included patients aged 60 or older with a diagnosis of dementia. The prescriptions were analyzed using the Lexi-Interact® database to identify possible potential drug-drug interactions. RESULTS: The study included 97 participants. Sixty-one patients (62.9%) had at least one clinically important potential drug-drug interactions (risks C and D). Of the 264 interactions identified, 23 (8.7%) were classified as risk D, 14 were pharmacodynamics and nine pharmacokinetic. CONCLUSION: The results of this study suggest an increased frequency in the occurrence of clinically significant potential drug-drug interactions in dementia patients. This reinforces the need for drug-drug interaction studies in specific populations.